Germanium-tin p-i-n photodetectors integrated on silicon grown by molecular beam epitaxy - Werner, J.; Oehme, Michael; Schmid, M.; Kaschel, M.; Schirmer, A.; Kasper, E.; Schulze, J. (Applied Physics Letters, 2011)
GeSn heterojunction p-i-n diodes with a Sn content of 0.5% are grown with a special low temperature molecular beam epitaxy. The Sn incorporation in Ge is facilitated by a very low temperature growth step in order to suppress Sn surface segregation. Diodes with sharp doping transitions are realized as double mesa structures with a diameter from 1.5 up to 80 μm. An optical responsivity of these GeSn diodes of 0.1 A/W at a wavelength of λ=1.55 μm is measured. In comparison with a pure Ge detector the optical responsivity is increased by factor of 3 as a result of Sn caused band gap reduction. © 2011 American Institute of Physics.
CRIS-Team Scopus Importer:2021-06-29